BAAMBOOZLE IN ENGLISH LANGUAGE LEARNING: A SIMULATION OF EDUCATIONAL GAMIFICATION FOR ENGLISH LANGUAGE LEARNERS (ELLS) - Fitria, Tira Nur (ELite Journal : International Journal of Education, Language and Literature, 2026)
This research simulates the creation of Baamboozle as an educational gamification for English language learners. This research is descriptive qualitative research. The analysis shows that Baamboozle emerges as a user-friendly platform facilitating interactive quiz game creation and play, enhancing learning engagement and enjoyment. Its intuitive design and simple registration process grant easy access to a diverse array of educational resources and games. Key features like My Library, Games, Blog, and Search Games equip users with comprehensive tools for organizing, discovering, and accessing tailored quiz games. Baamboozle's clean interface and vibrant graphics foster an inviting atmosphere conducive to interactive learning experiences. Users can leverage its game creation features, such as visual elements and privacy options, to customize learning materials according to their preferences. Moreover, Baamboozle fosters collaboration and discussion among users, enriching the learning journey. Following the provided steps, users can effortlessly generate personalized quiz games to supplement English language learning. Baamboozle proves invaluable for enhancing English language education through engaging educational game creation. Its user-friendly interface empowers teachers to design games aligned with curriculum objectives and student interests, fostering creativity and content integration. Utilizing features like timers and leaderboards adds competition and motivation to the learning process. Support and training ensure effective Baamboozle utilization, maximizing its potential to enhance students' English proficiency. Prioritizing creativity, content integration, student engagement, regular evaluation, feature utilization, collaboration, and ongoing support and training can optimize Baamboozle's role in English language education.